Pupillary Response to Cognitive Demand in Parkinson’s Disease: A Pilot Study - Kahya, Melike; Moon, Sanghee; Lyons, Kelly E.; Pahwa, Rajesh; Akinwuntan, Abiodun E.; Devos, Hannes (Frontiers in Aging Neuroscience, 2018)
Previous studies have shown that pupillary response, a physiological measure of cognitive workload, reflects cognitive demand in healthy younger and older adults. However, the relationship between cognitive workload and cognitive demand in Parkinson’s disease (PD) remains unclear. The aim of this pilot study was to examine the pupillary response to cognitive demand in a letter-number sequencing (LNS) task between 16 non-demented individuals with PD [age, median (Q1-Q3): 68 (62-72); 10 males] and 10 control participants [age: 63 (59-67); 2 males], matched for age, education, and Montreal Cognitive Assessment scores. A mixed model analysis was employed to investigate cognitive workload changes as a result of incremental cognitive demand for both groups. As expected, no differences were found in cognitive scores on the LNS between groups. Cognitive workload, exemplified by greater pupil dilation, increased with incremental cognitive demand in both groups (p = 0.003). No significant between-group (p = 0.23) or interaction effects were found (p = 0.45). In addition, individuals who achieved to complete the task at higher letter-number (LN) load responded differently to increased cognitive demand compared with those who completed at lower LN load, regardless of disease status (p < 0.001). Overall, the findings indicated that pupillary response reflects incremental cognitive demand in non-demented people with PD and healthy controls. Further research is needed to investigate the pupillary response to incremental cognitive demand of PD patients with dementia compared to non-demented PD and healthy controls.